Analysis of Literacy Program Based on Ability Level of Students in Elementary School - Arif widodo; Umar Umar (Sean Institute, 2021)
Learning based on student ability is one of the new approaches in the learning model. In general, learning is based on the class or age of students. This study aims to analyze whether the ability-based learning model is effective in improving students' abilities, especially in learning basic literacy. The study used a qualitative descriptive approach. The research location is at SDN Persil. Collecting data using observation, interviews, and documentation. The research subjects were 99 students. The results of the study indicate that ability level-based learning can improve students' basic literacy skills. The indicator of the increase in students' abilities can be seen from the increasing percentage of the number of students who advance to the story level.